Water and Air Quality Monitoring System based on the Internet of Things - Primantara, Komang Try Wiguna Adhitya; Wira Bhuana, Putu; Doran, Kyle (Lontar Komputer : Jurnal Ilmiah Teknologi Informasi; Vol 12 No 3 (2021): Vol. 12, No. 03 December 2021, 2021)
Environmental pollution is a global issue that occurs at this time. It is caused by various human activities that produce pollutants that endanger their lives. By utilizing current technology, it is possible to design a Water and Air Quality Monitoring System based on the Internet of Things to monitor air and water quality quickly and in real-time in the surrounding environment. The users can access this system via the web and Android / IOS mobile applications that display the data obtained by the sensor in the form of real-time graphics of water and air conditions. In addition, this system consists of several sensor nodes in charge of providing field data regarding the parameters used as the basis for assessing water and air quality according to the applicable standards in Indonesia. Sensors for water using a Turbidity Sensor, DS18B20 Sensor, PH Sensor, DHT 11, and TDS (Total Dissolved Solids) Sensor. Sensors for air consist of the DHT11 sensor, the MQ-7 sensor, the MQ-135 sensor, and the dust sensor GP2Y1010AU0F.